APPLICATION OF SMART BUILDING CONCEPT IN UNMANNED AERIAL VEHICLE (UAV) RESEARCH AND DEVELOPMENT TECHNOLOGY CENTER BUILDING - Jody Darmawan; Anisa Anisa; Luqmanul Hakim (Ide dan Dialog Desain Indonesia (Idealog), 2021)
The development of technology in the modern era has now provided many advantages in every need, one of the technologies that are currently developing are Unmanned Aerial Vehicle (UAV). Unmanned aircraft technology development can be utilized for the country of Indonesia because the State of Indonesia is an archipelagic country, almost part of Indonesia is not well monitored. This technology is expected to contribute greatly, especially in maintaining the security of borders and sovereignty of NKRI and aims to provide a boost for the research and technology development of unmanned aircraft. To be able to answer the problem is done study, observation, and interview related issue that happened, hence can be made one draft building concept of Research Center and Development of Technology of Unmanned Aircraft with Concept of Smart Building. This smart building concept aims to translate the character of the building which will become a high-tech research and development center building, by utilizing the automation system in the building and utilizing the surrounding environmental conditions by optimizing the energy produced by nature. It is hoped that the results of this building design can provide solutions to the problems faced, as well as add supplies for science and solutions related to the planning and design of the Research and Development Center for Unmanned Aircraft Technology with the Smart Building Concept in Kemayoran. Keywords: Research and Development Center, Smart Buildings, Unmanned Aerial Vehicle (UAV).